Experiences with Queen Bees: A South African study exploring the reluctance of women executives to promote other women in the workplace - Z. Johnson; B. Mathur-Helm (South African Journal of Business Management, 2011)
This study explores the experiences of women executives and senior managers in South Africa in respect of the Queen Bee syndrome. Queen Bee behaviour is a term used to describe women executives that, after reaching senior positions, alienate other women and hence prevent more junior women from advancing through the ranks. Such behaviour has in the past specifically been observed in corporate environments with a tradition of male domination. This study specifically focussed on the banking sector as an example of a previously male-dominate environment.Twenty-five women executives and senior managers from South Africa's five national retail banks were interviewed to obtain data on their unique personal experiences and perceptions of Queen Bee behaviour. The qualitative data were then content-analysed.This study is one of the first studies that reports on Queen Bee behaviour in South Africa, and confirms the existence of Queen Bee behaviour in South Africa, despite the efforts in the corporate world to advance the gender cause. While this paper does not provide evidence that women's advancement and growth in corporate organisations are solely reliant on the support and assistance of other women it, however, indicates the constraints of a hierarchical and male lead work culture in most organisations that could be a block to the promotion of professional women.Future studies are required to investigate the other sectors and to develop tools to detect and discourage Queen Bee behaviour.
Keywords: 650